2018
DOI: 10.1371/journal.pone.0191391
|View full text |Cite
|
Sign up to set email alerts
|

SUMO targeting of a stress-tolerant Ulp1 SUMO protease

Abstract: SUMO proteases of the SENP/Ulp family are master regulators of both sumoylation and desumoylation and regulate SUMO homeostasis in eukaryotic cells. SUMO conjugates rapidly increase in response to cellular stress, including nutrient starvation, hypoxia, osmotic stress, DNA damage, heat shock, and other proteotoxic stressors. Nevertheless, little is known about the regulation and targeting of SUMO proteases during stress. To this end we have undertaken a detailed comparison of the SUMO-binding activity of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Our group and others have reported that Senp1 regulates the activity of many transcription factors, including specificity protein1 (Sp1) in vivo and in vitro [ 9 , 13 , 14 , 17 , 29 ]. The Senp family regulates Sumo homeostasis in eukaryotic cells [ 30 ]. Dysregulation or imbalance between the Sumoylation and deSumoylation processes has been implicated in a wide variety of degenerative diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Our group and others have reported that Senp1 regulates the activity of many transcription factors, including specificity protein1 (Sp1) in vivo and in vitro [ 9 , 13 , 14 , 17 , 29 ]. The Senp family regulates Sumo homeostasis in eukaryotic cells [ 30 ]. Dysregulation or imbalance between the Sumoylation and deSumoylation processes has been implicated in a wide variety of degenerative diseases [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Next, the cells were incubated with 0.1M glycine-HCL (pH 2.0) for 10 seconds. The pH was immediately neutralized with 500μL of 10X SPB (500mM Tris-HCL, pH 8.0 2% NP-40, 1.5M NaCl) (Peek et al, 2018)…”
Section: Expression Of Kmutag-fl and In Vitro Assaysmentioning
confidence: 99%
“…We recently developed a novel SUMO-trapping protein from a thermotolerant yeast, Kluyveromyces marxianus (Km) (Peek et al, 2018). Specifically, we generated a catalytically inactive recombinant SUMO-trapping fragment of the UD domain of Ulp1 (the yeast SUMO protease), termed KmUTAG.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations